Investigating the dynamics of Plasmodium falciparum gametocyte carriage in expectant women under intermittent preventive treatment with sulfadoxine-pyrimethamine in Kilifi, study protocol [version 2; peer review: 3 approved] - Isabella Oyier; Martin Rono; Mainga Hamaluba; Patience Kerubo Kiyuka; Nelson Ouma; Mark Muricho; Amek Nyaguara; Charles Muiruri (Open Research Europe)
Introduction Malaria in pregnancy remains a public health problem. The World Health Organization (WHO) recommends intermittent preventive treatment with sulfadoxine-pyrimethamine (IPTp-SP) to all pregnant women in moderate to high malaria transmission areas. Kenya's Ministry of Health recommends at least three doses of IPTp-SP (IPTp-SP3 +) to pregnant women in regions where malaria is endemic. Although SP remains cost-effective and effective for IPTp, there are two main challenges with the use of SP: i) widespread use of SP can lead to an increase in the prevalence of drug resistance molecular markers, including those encoding for Plasmodium falciparum dihydrofolate reductase (dhfr) and Pf dihydropteroate synthase (dhps) and ii) SP, used either for curative or preventive treatment, is associated with microscopic and sub microscopic gametocytaemia, both of which contribute to sustained malaria transmission. Our study aims to investigate the dynamics of Plasmodium falciparum gametocyte carriage in pregnant women under intermittent preventive treatment with sulfadoxine-pyrimethamine in Kilifi. Methods This will be a cross-sectional study and will recruit (N=462) expectant women attending antenatal care (ANC) clinics in four health facilities within the Kilifi Health and Demographic Surveillance Sites: Njunju, Pingilikani, Ngerenya, and Kilifi County Teaching and Referral Hospital (KCTRH). To be recruited into our study, women will need to be in their first or second pregnancy when they are more likely to have malaria and should have had at least one dose of sulfadoxine-pyrimethamine. Expected application of results Our study will provide information on the current status of malaria during pregnancy in Kilifi and the prevalence of gametocytes among expectant mothers on IPT-SP. The results of this study may help inform new interventions to prevent malaria during pregnancy, including adding a third drug to SP with probable gametocytocidal effects.